Species diversity and prey items of amphibians in Yoddom Wildlife Sanctuary, northeastern Thailand - Prapaiporn Thongproh; PRATEEP DUENGKAE; PRAMOTE RATREE; EKACHAI PHETCHARAT; WASSANA KINGWONGSA; WEEYAWAT JAITRONG; YODCHAIY CHUAYNKERN; CHANTIP CHUAYNKERN (Society for Indonesian Biodiversity, 2019)
Abstract. Thongproh P, Duengkae P, Ratree P, Phetcharat E, Kingwongsa W, Jaitrong W, Chuaynkern Y, Chuaynkern C. 2019. Species diversity and prey items of amphibians in Yoddom Wildlife Sanctuary, northeastern Thailand. Biodiversitas 20: 2718-2732.  Amphibian occurrence within Yoddom Wildlife Sanctuary, which is located along the border region among Thailand, Cambodia, and Laos, is poorly understood. To determine amphibian diversity within the sanctuary, we conducted daytime and nocturnal surveys from 2014 to 2017 within six management units. We recorded 26 amphibian species and two additional unidentified taxa from two orders (Anura and Gymnophiona) and six families. Four of the encountered species are new records for Ubon Ratchathani, (Kalophrynus interlineatus, Microhyla berdmorei, Micryletta inornata, and Chiromantis nongkhorensis). In addition to observational surveys, we investigated amphibian prey items via fecal pellet analyses. Prey items comprised mainly animals (85% from class Insecta), but 9% of species consumed both plants and animals. Among insects, Coleoptera and Hymenoptera were the most abundant prey (35% and 31%, respectively). In addition, we observed one case of Ichthyophis kohtaoensis consuming an earthworm and an incident of cannibalism in Sylvirana mortenseni. Finally, due to illegal logging activities and active landmines, surveys were limited to the secure regions within the sanctuary. Thus, we noted that further species might remain unidentified within Yoddom Wildlife Sanctuary due to this limitation.